CERITA RAKYAT BERBASIS MOBILE UNTUK ANAK SEKOLAH DASAR - Jayanta, I Nyoman Laba; Susiani, Ketut (Jurnal Ilmiah Sekolah Dasar, 2017)
This research aimed at developing a mobile-based folklore with local wisdom inserted for elementary school students in which the language used is Balinese. The present research was applying System Development Life Cycle (SDLC) research method. The study underwent five steps, that is, Analysis, Design, Implementation, Testing, and Evaluation. The first step of this research was need analysis of the application. In this step, the need analysis of content application and application development was done. The next step was application design including flowchart design and storyboard. The steps of development was using application design plan. In this step, the result was Balinese folklore application with local wisdom inserted. To test the function of this application, an application test was done by applying black box method. This evaluation was conducted by involving teacher and elementary school students at SDN 3 Banyuning. The result of evaluation showed that it was found 20 out of 25 students liked this folklore application with local wisdom inserted.